Hubungan Hipertensi Dengan Tingkat Kecemasan Pada Lansia Di Puskesmas Banjardawa - Hidayati, Hanifia Ilma; Iskim Luthfah; Moch. Aspihan; Abrori (An-Najat, 2025)
Elderly people who suffer from hypertension often experience anxiety because they feel unable to carry out their usual activities. This anxiety has a significant impact, because it can cause narrowing of blood vessels which leads to an increase in blood pressure above normal limits. This increase in blood pressure causes higher levels of anxiety in the elderly. It is hoped that this research will be an effort to prevent or reduce the level of anxiety in elderly people who suffer from hypertension and maintain the quality of life of elderly people in the future. of this research is to describe hypertension in the elderly and find its relationship with anxiety levels at the Banjardawa Community Health Center, Pemalang City. This research uses a correlational quantitative research type with a cross-sectional approach, and uses the Spearman Rank Test. The population in this study were elderly patients with hypertension at the Banjardawa Community Health Center, Pemalang City. The sampling technique is using the Purposive Sampling technique. The technique for collecting hypertension data is using a sphynomanometer with an ordinal scale, while for anxiety levels using a questionnaire with an ordinal scale. From the results of research using analysis tests which have been carried out using the Spearman Rank coefficient test, it is known that the close relationship between the two variables is 0.552, so it can be concluded that the relationship between the two variables shows a moderate positive relationship. The coefficient figure is 0.552 (positive) in the same direction, thus indicating a moderate positive relationship. This means that the higher the level of anxiety, the higher the blood pressure. The results of this study show that there is a significant relationship between hypertension and anxiety levels in the elderly at the Banjardawa Pemalang health center.